Metode Newton-Steffensen untuk Menentukan Hampiran Akar Persamaan Tak Linier - Khairunisa Khairunisa; Muhammad Subhan; Meira Parma Dewi (Journal of Mathematics UNP, 2018)
Abstract –Newton-Steffensen method is one of numerical method for finding root of nonlinear equation. This method is modified method from Newton-Raphson method. The purpose of this research is to review the iteration formula, compile the algorithm, and analyze the order of convergence. This research is theoretical research. Which is a literature study based on the relevant sources. Based on the result, the algorithm applied to a computer program. The order of convergence of Newton-Steffensen method is three so the method is faster than Newton-Raphson method.